Extra-glandular manifestations with Sjögren’s Syndrome: Case Series in Bangladesh - Akter, Benojeer; Noor, Jamila; Chowdhury, Mohammed Baieas; Haque, Fahim; Iqbal, Asif; Raihan, Jannatul (Journal of Medicine, 2025)
Background: Sjögren’s syndrome (SS) is a chronic autoimmune disease that is mainly characterized by lymphocytic infiltration of the exocrine glands, leading to sicca symptoms. Extraglandular manifestations (EGMs) involving more than one organ system influence prognosis.Though SS is gaining global recognition, information from Bangladesh remains limited. The present case series aims to put into perspective the clinical spectrum of EGMs in SS patients within the context of a Bangladeshi tertiary care. Methods: We retrospectively analyzed patients with primary SS, based on the 2016 ACR/EULAR classification criteria,who were admitted to the rheumatology outpatient clinic of Shaheed Suhrawardy Medical College Hospital between July 2024 to December 2024. Clinical data were analyzed for demographic data, serologic features, and reported extra-glandular manifestations on renal, ocular, neurology, dental, endocrine, and hematological systems. Results: 04 cases of Sjögren’s syndrome were diagnosed with extra-glandular manifestations like non-eruption of teeth, central chorioretinopathy, thrombocytopenic purpura, renal tubular acidosis over 02 years. Sjögren’s syndrome was diagnosed based on the 2016 ACR/EULAR classification criteria, including clinical features, Schirmer’s test, and autoantibodies. Biopsy was not performed. Conclusion: SS extraglandular manifestations are still underdiagnosed in Bangladesh and can be one of the reasons for delay in diagnosis and less-than-ideal management. Our findings emphasize the need for systematic screening protocols and physician awareness of the multi-system nature of the disease. Prospective studies are necessary to ascertain the true prevalence and clinical impact of EGMs in the Bangladeshi population. J MEDICINE 2025; 26(2): 142-145